Risk Factor Analysis of Chronic Energy Deficiency (CED) in Pregnant Women at Kassi-Kassi Community Health Center in July-December 2023 - Andi Sabrina (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Chronic Energy Deficiency (CHD) is a condition of malnutrition characterized by upper arm circumference ≤ 23.5 cm, if it occurs in pregnant women who can endanger pregnant women and their fetuses. This study aims to analyze the risk factors of SEZ in pregnant women at Kassi-Kassi Health Center, Makassar, during the period July to December 2023, with an observational analytic design and cross-sectional approach. The study population included 767 pregnant women, and the sample consisted of 88 people selected according to purposive sampling criteria, which was assessed by calculating the Slovin formula, with 33 respondents identified as having SEZ. Data were collected through questionnaires to measure knowledge, dietary intake, and disease history, and secondary data from the MCH book to determine parity. Data were analyzed using frequency distribution table and Chi-square test. The results showed that the prevalence of SEZ was quite high, namely 37.5%.. Data analysis found a significant relationship between knowledge (p=0.043), income (p=0.033), and food intake (p=0.015) with the incidence of SEZ, while disease history (p=0.640) and parity (p=0.502) showed no significant relationship.